Nurses’ knowledge, attitude and practice on eye care in critical care area at Hospital Universiti Sains Malaysia - Hashim, Nur Sabrina (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Eye care is an essential component of nursing care for critically ill patients who are particularly vulnerable to eye disorders because their illness and treatment can compromise ocular protective mechanisms. Hence, eye care is important in critical care area. However, lack of eye care studies is a common issue across the globe. The aimed of this study to determine the level of nurses’ knowledge, attitude and practice on eye care in critical care ward at Hospital USM. Besides, this study also investigated the association and correlation of demographic data between nurses’ knowledge, attitude and practice on eye care. This study was conducted using a self-administrated questionnaire and the data were collected from 118 nurses in five kinds of ICUs at HUSM. The findings revealed that majority of the respondents had unsatisfactory level of knowledge (94.1%). In contrast, majority of the respondents had satisfactory level on attitude (94.1%) and practice (89.8%) on eye care. In addition, the results showed that two sociodemographic factors significantly associated with nurses' knowledge on eye care were gender (p=0.027) and years of experience working as a nurse (p=0.041). Plus, the findings also summarized that there is statistically significant correlation between nurses’ attitude towards the importance of eye care and eye care practices in mechanically ventilated patients (r=0.51, p=0.000).